Determination of protein phosphorylation by extracellular signalregulated kinase using capillary electrophoresis and matrix-assisted laser desorption ionization time-of-flight mass spectrometry - Nam, HS; Ban, E; Yoo, E; Yoo, YS (ELSEVIER SCIENCE BV, 2002)
Extracellular signal-regulated kinase (ERK) is a key regulatory enzyme mediating cell responses to mitogenic stimulation and is one of the key components in linking growth factor receptor activation to serine/threonine protein phosphorylation processes. Phosphorylation reaction by ERK plays an important role in many signal transduction pathways. ERK phosphorylates numerous substrates such as MBP, micrombule-associated protein 2 (MAP2) and nuclear protein. In particular, MBP is a substrate commonly employed for the detection of ERK activity and contains the consensus primary sequence PRT97P. In this paper, we compared the degree of the phosphorylation reaction of MBP substrate peptides by ERK with the three different MBP substrate peptides, MBP1(KNIVTPRTPPPSQGK), MBP2(VPRTPGGRR) and MBP3(APRTPGGRR) in order to select an efficient substrate peptide for phosphorylation reaction by ERK. The results showed that the MBP3 peptide is the most efficient substrate for phosphorylation reaction by ERK. Using MBP3 peptide, the phosphorylation reaction of MBP by ERK was monitored with both matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) and capillary electrophoresis (CE). Our results demonstrate the feasibility of the CE method, the method being a simple and reliable technique in determining and characterizing various kinds of enzyme reaction especially including kinase enzymes. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: ZONE-ELECTROPHORESIS; PHOSPHATASES; ASSAY; THREONINE; SERINE